2004
DOI: 10.1111/j.1447-0756.2004.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of quantitative ultrasound calcaneus measurement in case finding for osteoporosis in Thai postmenopausal women

Abstract: Bone mass density measurement for predicting osteoporosis using QUS had a very low sensitivity and was not good enough to replace the standard tool (DXA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…A large sample of routine clinical patients reflects everyday clinical practice and therefore might be more appropriate for the estimation of T score thresholds 47 . On the other hand, it is well known that there is a wide variety of reasons for patients' referral for bone status assessment.…”
Section: Discussionmentioning
confidence: 99%
“…A large sample of routine clinical patients reflects everyday clinical practice and therefore might be more appropriate for the estimation of T score thresholds 47 . On the other hand, it is well known that there is a wide variety of reasons for patients' referral for bone status assessment.…”
Section: Discussionmentioning
confidence: 99%
“…In 4 out of the 15 papers included, the authors concluded that heel ultrasound cannot replace densitometry because of low conformity between the two methods . Sensitivity values of QUS compared with densitometry were 22 to 100% (mean 72.5 ± 20.8%) and specificity of 36.5 to 94% (65.4 ± 17.8%).…”
Section: Resultsmentioning
confidence: 99%
“…For cases in which the optimal T-score cutoff was calculated, the sensitivity and specificity are shown with respect to the optimal T-score value for diagnosis of In 4 out of the 15 papers included, the authors concluded that heel ultrasound cannot replace densitometry because of low conformity between the two methods. [16][17][18][19] Sensitivity values of QUS compared with densitometry were 22 to 100% (mean 72.5 6 20.8%) and specificity of 36.5 to 94% (65.4 6 17.8%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Como método de traigem populacional tem sido feito por vários autores em diferentes países, dentre os quais citamos: Pluskiewicz (1999), que avaliou uma população polonesa de 740 mulheres (entre normais e com osteoporose) e 224 homens (entre normais e com osteoporose); Hadji (1999a), avaliou uma população de 1333 mulheres alemãs saudáveis com média de idade 50,5±11,5 anos; Kim (2000), avaliou uma população de 790 mulheres coreanas de idade entre 20 e 75 anos; Wehbe (2003), avaliou uma população de 4320 mulheres libanesas, para criar uma fonte de dados, de idade entre 20 e 79 anos e Panichkul (2004), avaliou uma população de 107 mulheres tailandesas com osteoporose para fazer comparação entre os parâmetros QUS e DXA.…”
Section: Novas Aplicações Da Ultrassonometria óSseaunclassified